Gold medal ready (2019)
The Gold Medal Ready program aims to support medal potential athletes and coaches be "ready" for the stress, pressure and expectation to perform to their best and win at the Tokyo 2020 Olympic Games. More than 150 athletes and coaches will participate in the program prior to the 2020 Olympics including education, skill development, mentoring and specifically designed activities delivered in partnership with the Australian Army`s Special Operations Command. It enables our top athletes to develop in order to reach their peak performance and sustain that under Olympic conditions.